FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU LANSIA TERHADAP PEMANFAATAN POSYANDU LANSIA DI DESA PAGERAJI - Ayuningsih, Desi; Ulfah, Mariah; Kurniawan, Wasis Eko (STIKES Suaka Insan, 2023)
Pageraji Village is recorded as having the largest population in Cilongok District, Banyumas Regency. This village also has the largest number of elderly people who have not utilized the Posyandu. The purpose of this study was to identify the factors that influence the behavior of the elderly toward the utilization of the Posyandu. A total of 91 respondents were selected using an accidental sampling technique. Data collection was carried out using the Health Belief Model (HBM) questionnaire. The data collected was then analyzed using univariate and bivariate statistics. This study shows that there is a moderate relationship between 44 respondents' (48.4%) perceived vulnerability to posyandu (48.4%) p value = 0.05 towards the use of the Posyandu, moderate perceived benefits of 53 respondents (58.2%) p value <0.05 on the utilization of the Posyandu, and the perceived barriers were moderate, namely 43 respondents (58.2%). The value of p value <0.05 on the utilization of the Posyandu. This study concludes that there was a relationship between vulnerability factors, perceived benefits, and obstacles to the use of the elderly Posyandu. Keywords: Elderly behavior, Posyandu utilization, Posyandu, Elderly